Factors associated with avoidance of emergency department visits in Portugal during the pandemic. (20th October 2021) - Lopes, S; Soares, P; Gama, A; Pedro, AR; Moniz, M; Laires, P; Goes, AR; Nunes, C; Dias, S
Abstract: Background: Avoiding an emergency department (ED) visit risks irreversible negative consequences for patients' health. EDs are a frequent access point to the Portuguese health system. Previous studies have shown that patients may avoid visiting ED during the pandemic. This study aims to identify factors associated with avoidance of ED visits in Portugal during the COVID-19 pandemic. Methods: We used data from a community-based survey, "COVID-19 Barometer: Social Opinion", which includes healthcare utilisation, health status, and risk perception in Portugal from 11th April 2020 to 16th April 2021. We included respondents that reported having needed ED care. Data were collected on sociodemographics, health status (comorbidities, mental health), risk perception (COVID-19 and complications), level of trust in health services and self-assessment of the severity of the reason for ED visit. The outcome of interest was the decision to avoid ED care. We used logistic regression to identify factors associated with the decision to avoid ED. Results: Preliminary data showed that 914 respondents reported needing ED care (74.8% female; mean age 43 years). From those, 224 (25%) decided to avoid ED care. ED visits avoidance was higher during lockdowns (28%). People reporting specific comorbidities (cardiac, autoimmune, respiratory) avoided ED more than those without them. Perception of no severe reason for ED visit, poor mental health, perception of higher risk of COVID-19 and complications, and low trust in health services response to the pandemic were associated with higher odds of ED visit avoidance. Conclusions: People avoiding ED visits represented a considerable share. The decision to avoid ED visit was associated with clinical characteristics, but the perception of risk and assessment of the context and health system response also played a role in decision making. Key messages: The effect of avoided ED visits on health should be a research and policy concern. People with certain comorbidities or perception of high risk of COVID-19 and complications may be closely monitored.